PENYULUHAN INSTALASI LISTRIK YANG AMAN DAN HANDAL UNTUK PERUMAHAN - Gunawan Toto Hadiyanto; Mardiono, Djoko Anwar; Jumadril, Jumadril JN; Kumala Sari, Intan; Saptarika, Ria; Salim, Kalbin; Apriyanto, Bambang; Nanra, suwadi; Anwar, Nur Effendi; Kusuma Raharjo, Adriene (LPPM-Universitas Batam, 2025)
The electrical energy demand in currently era is a very vital need, the electrical energy demand is spread almost to all human life needs, so it is only right if there is a reliable energy supply, There fact are that many people's homes and also public places area or mosque and public facilities have poor electrical installations and need to repair. These also happen with the electrical facilities in the public facilities of Teluk Mata Ikan Village, Nongsa District, Batam City. The reality is that most people still do not understand about electrical installations and there are still many electrical installations that do not comply with general regulations on electrical installations, In addition, there are still many electrical installation connections made by the community themselves that do not comply with the provisions. So this time Community Service is carried out by providing counseling about the importance of reliable and safe electrical installations. and go directly to the location to show how to install it properly, correctly and safely. By holding community service (PKM), residents are expected to understand how to install electricity properly, correctly and safely. The equipment selected for installation in an electrical installation must meet applicable standards and must be in accordance with environment. The installation of equipment must comply with the provisions in PUIL standard, and suitable according to the equipment manufacturer's instructions. To increase public knowledge and understanding of the importance of electrical hazards achiefments, this activity needs to be carried out continuously.